ANALISIS RASIO VOLUME KENDARAAN TERHADAP KAPASITAS RUAS JALAN MAJALAYA-RANCAEKEK KABUPATEN BANDUNG - Muzaki, Asep Irvan fajar; Saepudin, Uu; Defiana, Yanti (Jurnal Ilmiah Teknik Sipil, 2026)
The increasing transportation activities along the Majalaya–Rancaekek road segment, Bandung Regency, have caused capacity limitations and a decline in service levels. This study aims to analyze the ratio of traffic volume to capacity (Q/C) and determine the Level of Service (LOS) based on the Indonesian Highway Capacity Manual (PKJI) 2023. Methods include peak-hour traffic volume surveys, side-friction observations, free-flow speed analysis, road capacity calculation, degree of saturation, and LOS classification. The results show an average traffic volume of 1603 pcu/hour with a capacity of 2037.95 pcu/hour, resulting in a degree of saturation (DS) of 0.75. This condition places the road segment in LOS D, characterized by dense traffic flow, reduced speed of 36.9 km/h, and lower travel comfort. Medium-level side friction from industrial, commercial, and market activities was identified as the dominant factor. After improvements such as lane optimization and side-friction control, capacity increased to 2289.84 pcu/hour, lowering DS to 0.66 and improving LOS to C. The study concludes that capacity enhancement and side-friction management are essential to improve traffic flow efficiency and user comfort.